Arus Kas Dan Kesulitan Keuangan Perusahaan (Studi Empiris Pada Perusahaan Subsektor Coal Mining yang Terdaftar Dalam IDX SCM Liquid di Bursa Efek Indonesia Periode 2017 â€“ 2021) - Ayu Puspitaningtyas (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
Â The study evaluates the influence of cash flow on the financial distress of company under study is caol mining sector listed enterprises on IDXSCM Liquid in the Indonesia stock market from 2017 to 2021. We use the data collected from the financial statements of 4 company enterprises listed on the IDX SCM Liquid from 2017 to 2021 in the idx database. The quantile regression method was employed to analyze the effect of cash flow on the financial distress of listed coal mining subsector companies. The results show that the cash flow from operating activities and the cash flow from financial activities have negative relationships with financial distress. However, the cash flow from investing activities has a positive relationship. Based on experimental results, the study proposes some recommendations on cash flow forecasting, building an optimal budget model to help business managers have appropriate cash flow management policies to reduce the risk of financial distress